2020
DOI: 10.7759/cureus.10734
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Colorectal Cancer: A Holistic Approach and Review of the Clinical Utility

Abstract: Vitamin D is well known for its effects on the homeostasis of calcium and phosphorus. Lately, considerable research has brought the extra-skeletal role of vitamin D under the spotlight, including its anti-cancer activity. Colorectal cancer (CRC) is the most extensively studied neoplasia that has been observed to be affected by vitamin D; the list includes breast, prostate, and ovarian cancer. This review aims to shine a light on the influence of vitamin D over CRC and to further understand its ability to be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This appears to be dependent on expression of the VDR. Calcitriol promotes VDR/β-catenin binding, reduces the amount of β-catenin bound to TCF, induces expression of the CDH1 gene encoding E-cadherin (which sequesters β-catenin), and increases extracellular expression of the Wnt inhibitor DKK-1 [ 19 , 34 - 38 ].…”
Section: Mechanisms Of Vitamin D Action In Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears to be dependent on expression of the VDR. Calcitriol promotes VDR/β-catenin binding, reduces the amount of β-catenin bound to TCF, induces expression of the CDH1 gene encoding E-cadherin (which sequesters β-catenin), and increases extracellular expression of the Wnt inhibitor DKK-1 [ 19 , 34 - 38 ].…”
Section: Mechanisms Of Vitamin D Action In Crcmentioning
confidence: 99%
“…Vitamin D exerts an anti-inflammatory effect by interfering with the synthesis of prostaglandins, stress-activated kinase signaling, and production of proinflammatory cytokines, as well as acting as a potent inhibitor of tumor cell-induced angiogenesis, inhibiting stress-activated kinase signaling, and inducing mitogen-activated protein kinase, all of which have an anti-cancer effect. Vitamin D-activated maternally expressed gene 3 ( MEG3 ) suppresses glycolysis in CRC by promoting degradation of c-Myc [ 8 , 37 , 42 , 43 ]. The anti-cancer effects mediated by Vitamin D signaling are illustrated in Figure 2 .…”
Section: Mechanisms Of Vitamin D Action In Crcmentioning
confidence: 99%
“…The confinement associated with the global pandemic has certainly played a key role in determining the serum VitD levels of patients with COVID-19 infection and solid neoplasms, such as colorectal, breast, lung, ovarian, bladder, prostate, and thyroid cancer. VitD levels, in addition to VRD polymorphisms, have proven to impact the outcomes of these patients [ 35 , 69 , 70 , 71 , 72 , 73 , 74 ]. However, studies have found contrasting results.…”
Section: Vitamin D and The Immune Systemmentioning
confidence: 99%
“…Vitamin D and its analogues are potent inhibitors of colorectal cancer growth and metastasis. Some recent studies have defined the intersections between the β -catenin-TCF pathway (a known contributor to colorectal cancer progression) and the vitamin D receptor (VDR) pathway, shedding light on the basic mechanisms, [46,47,48].…”
Section: Patientsmentioning
confidence: 99%